1994
DOI: 10.1016/0168-6496(94)90014-0
|View full text |Cite
|
Sign up to set email alerts
|

Survival of genetically modified Pseudomonas fluorescens introduced into subtropical soil microcosms

Abstract: A genetically modified strain of Pseudomonas fluorescens and its parent showed grossly similar decline rates following introduction into subtropical clay and sandy soils. In unplanted clay soit at pH 6.9 and 25°C, population densities declined progressively from about 108 to 103 colony forming units (cfu) g−1 dry soil over 75 days, but in unplanted sandy soil the introduced populations could not be detected after 25 days. In clay soil at pH 8.7 or 4.7, or at environmental temperature, decay rates were enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Botelho et al (18) observed no difference in the size, structure and function of bacteria communities analyzed when a strain of P. fluorescens was introduced by seeds of maize. Guimarães et al (47,48) and Araújo et al (4,5,6) observed that a strain of P. fluorescens and its OGM were able to survival and/or colonize bulk soil and rhizosphere of maize. Moënne-Loccoz et al (100) results suggested that the root-associated Pseudomonas community of sugar beet seedlings was resilient to the impact that may be caused by a taxonomically related inoculant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botelho et al (18) observed no difference in the size, structure and function of bacteria communities analyzed when a strain of P. fluorescens was introduced by seeds of maize. Guimarães et al (47,48) and Araújo et al (4,5,6) observed that a strain of P. fluorescens and its OGM were able to survival and/or colonize bulk soil and rhizosphere of maize. Moënne-Loccoz et al (100) results suggested that the root-associated Pseudomonas community of sugar beet seedlings was resilient to the impact that may be caused by a taxonomically related inoculant.…”
Section: Discussionmentioning
confidence: 99%
“…II. Araújo et al (4) observed that fluorescent Pseudomonas were able to compete onto the rhizoplane of maize. The increase in the heterotrophic and total of gram negative communities indicated this competition ability.…”
Section: Ecological Aspects Of Pseudomonads In the Rhizospherementioning
confidence: 99%
“…The texture would affect the mechanical impedance which influences the root exudation [21]. The increase of carbohydrates in rhizospheric soil was shown to be more obvious in the sand than in the silt and clay fractions [16]. The negative influence of the clay fraction on the rhizosphere effect has also been stated by Heijnen et al [17], who have shown that amendment of a loamy sand soil with bentonite reduced the size of the rhizosphere effect.…”
Section: Discussionmentioning
confidence: 85%
“…Introduction of montmorillonite and illite in a natural soil was shown to increase the density of the indigenous populations of fluorescent pseudomonads [15]. Several papers have reported the better survival of introduced strains of fluorescent pseudomonads in fine‐texture soils or in soils amended with clay [16–20]. The survival of two strains of Azospirillum brasilense in 23 sterilized soils was correlated positively with their clay and organic matter content and negatively with their CaCO 3 and sand content [21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the difference in the host plant, one single genotype was found to dominate in all three hosts. Even in pseudomonads, several studies have shown that their survival varies with soil texture (Araujo et al . 1994).…”
Section: Discussionmentioning
confidence: 99%